Is the welfare state sustainable? Experimental evidence on citizens' preferences for redistribution - Ilja Neustadt; Peter Zweifel (Center for Economic Studies and ifo Institute (CESifo), 2010)
The sustainability of the welfare state ultimately depends on citizens' preferences for income redistribution. They are elicited through a Discrete Choice Experiment performed in 2008 in Switzerland. Attributes are redistribution as GDP share, its uses (the unemployed, old-age pensioners, people with ill health etc.), and nationality of beneficiary. Estimated marginal willingness to pay (WTP) is positive among those who deem benefits too low, and negative otherwise. However, even those who state that government should reduce income inequality exhibit a negative WTP on average. The major finding is that estimated average WTP is maximum at 21% of GDP, clearly below the current value of 25%. Thus, the present Swiss welfare state does not appear sustainable.
Keywords: C35; C93; D63; H29; 330; income redistribution; welfare state; sustainability; preferences; willingness to pay; discrete choice experiments; Sozialstaat; Einkommensumverteilung; Staatsquote; Willingness to pay; Diskrete Entscheidung; Test; Schweiz